Penggunaan Aplikasi Kamus Bahasa untuk Belajar Bahasa Inggris di EECC Kampung Inggris Pare - Hamidah, Fitria Nur; Sukya, Fadelis; Yanuarmawan, Dion; Widyastuti, Ratna; Arif, Saiful (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
This community service activity is an activity about using the Language Electronic Dictionary Application to learn English in EECC Pare English Village which has a purpose to socialize and to provide knowledge about the use and utilization of the Language Electronic Dictionary Application as an effective, fantastic and innovative learning medium in English language learning in EECC Pare English Village. The target audiences were the English tutors. The method which was used in this community service was the approach method, the implementation method which was consisted of the preliminary stage, the socialization and hearing stage, and the evaluation stage. The result of this community service showed that English tutors in EECC Pare English village could utilize and use the Electronic Language Dictionary application as an effective, fantastic and innovative English learning medium. In addition, this application media could be a motivation and very popular with learners who are learning English.